(untitled) (Revista de Estudos da Linguagem, 2024)
This paper aims to understand a polemical episode (Amossy, 2017) on social network Twitter headed by Xuxa Meneghel about the use of prisoners as human guinea pigs (Boyd; Ellison, 2008; Cabral, 2022; Kwak et al., 2010; Recuero; Zago, 2010), from the perspective of the Dialogical Model of Argumentation (Plantin, 2008). The analysis of internet users’ interactions was undertaken so that we could see the argumentative strategies used by interactants in contexts of disagreement of opinions, as is common in web 2.0 (Paveau, 2021). Disagreements are here part of a stase, like we may observe in DMA. After a detailed examination of the corpus, we noted the “spreading of the argumentative stasis”, that is, a divergence of opinions so deep that leads the interlocutor to the silence. It was verified that the polemical interactions were materialized by the use of ad hominem, ad personam and ad populum arguments (Grácio, 2013; Plantin, 2016; Walton, 2006), in order to invalidate, disallow and generalize the position of the opponent and to discourage interactional mechanics of the interaction, leading the actantial opponent to the abandon of the dialogue. Thus, we verified the supressing of the interlocutors’ voice, a procedure of the eristic ancient Rhetoric.